Gastric outlet obstruction due to peptic ulcer disease in a 5 years-old female child. Case report. June 23, 2022. (April 2023) - Negash, Samuel; Jembere, Tarekeng; Abera, Gersam; Kedir, Elias; Eshetu, Beza
Abstract: Introduction and importance: Gastric outlet obstruction (GOO) is a spectrum of congenital and acquired conditions that prevent the passage of gastric contents beyond the proximal duodenum. Peptic ulcer disease (PUD), which causes GOO, is extremely rare in children, with an incidence of 1 per 100, 000 live births. Because of the rarity of the disease in children, we report a case of GOO due to PUD in a 5-year-old child. Case presentation: We report a case of an acquired GOO due to PUD in a 5-year-old female child who presented with vomiting, weight loss, and epigastric pain of 3 months' duration. Her diagnosis of GOO secondary to PUD was made by upper gastrointestinal (UGI) endoscopy despite a negative stool H. pylori antigen. She was managed with proton pump inhibitor (PPI), which results in improvement of signs and symptoms. She has been on follow-up for the last 6 months and has remained asymptomatic. Clinical discussion: H. pylori -positive GOO is successfully treated with PPI and antibiotic therapy. The role of H. pylori therapy in PUD-related GOO is less clear, although eradication is warranted as a primary intervention. Conclusion: GOO secondary to PUD may occur in the absence of Helicobacter pylori infection (HPI). Our patient demonstrated response to medical management in the acute phase of ulceration. Highlights: Peptic ulcer disease is extremely rare cause of gastric outlet obstruction in children. Common cause of peptic ulcer disease in pediatric age is helicobacter pylori infection. Endoscopy is a useful examination to establish the diagnosis. H. pylori positive gastric outlet obstruction should be treated with PPI and antibiotic therapy. Some of the cases are H. pylori negative, and H. pylori tests may not always be reliable.